Improving Young Learner's Vocabulary By Using Hand Puppets (An Action Research) In Permata Sari Kid's School Boyolali - Isvandari, Yuliandhicha (2012)
In this research, the researcher did the research in A1 level of Permata Sari Kid's School of Boyolali. Here, the researcher proved that hand puppets can improve young learner's vocabulary. It is showed from the result of the increasing score of the students. The result of the research showed that the mean of the student's score before the research is 52,80 where 11 students include in low category, 8 students include in good category, and only 2 students include in very good category. In other words, it can be concluded that around 55% of the students could not reach the learning target. After the researcher applying the research, the mean of the student's score is 77,95 where only 2 students include in low category, 8 students include in good category and 11 students include in very good category. In the other words, only 10% of the students could not reach the learning target. It means that the student's vocabulary increase 25,15 point. The researcher proved that hand puppets are effective media to improve young learner's vocabulary. The implementation of hand puppets in this research was as media. The researcher combined hand puppets with a story. So, the students did role play in every topic based on the narration of the teacher. The students acted the figure of the story by using hand puppets. The strengths of this media were that they avoid student's boredom in learning and improve student's activeness and confidence. While the weaknesses were that they needed more budget (money), time, reparation and creativity. So, when the teacher taught by using this media, the teacher should be patient and dilligent to prepare the media.